Sociability on Location Based Mobile Games: An Ethnographic Research on Pokémon Go and Ingress in Istanbul - Tokgöz, Cemile; Polat, Burak (European Journal of Social Science Education and Research, 2020)
Physical space has become intertwined with digital information with the escalatory development of information and communication technologies such as ubiquitous computing, mobile and wearable devices, GPS technology, wireless networks, smart city applications and augmented reality. The relationship between urban space and location-based technology has transformed everyday life practices; and one of these life practices is playing game. Location based mobile games (LBMGs) are being played on streets and provide interaction with urban environments. Mobile devices become the interface between the player and urban space, and players experience the urban through the game narrative. Nowadays, the most popular LBMGs are Ingress and Pokémon Go. Although the both games were created by the same company and configured on the same map, they arouse different effects. LBMGs have a great potential to shape gaming experiences thus researching different effects of Ingress and Pokémon Go hold an academic importance. The difference between these two games can only be revealed by participating in game communities and conducting a qualitative research. Because of that, this study is built on an ethnographic research about Ingress and Pokémon Go; and the results of the research revealed the importance of sociability. In this study, firstly, LBMGs are defined and the influences of these games on everyday life are discussed. Secondly, the differences and similarities are examined between Ingress and Pokémon Go according to the analysis obtained from participant observation and in-depth interviews. Finally, the importance of sociability is emphasized and foresights are provided in the light of research results to contribute to the game studies.